(untitled) (Academic Journal of Internal Affairs, 2020)
This paper is about the theoretical issues of forensic identification and individualization, comparison and reconstruction. Identification may be considered as the core point of forensic sciences. During crime scene processing or data mining the identification has paramount relevance. Psychological and philosophical aspects of identification, individualization and the so-called ACE-V methodology are also covered.